Hyperandrogenemia in obese peripubertal girls: correlates and potential etiological determinants - Knudsen, K. L. (2010)
Obesity in peripubertal girls is associated with hyperandrogenemia (HA), which can represent a forerunner of polycystic ovary syndrome. However, not all obese girls demonstrate HA, and determinants of HA in obese girls remain unclear. We hypothesized that insulin and luteinizing hormone (LH) are independent predictors of free T concentration in obese girls. To assess this further, fasting morning blood samples were collected from 92 obese (body mass index-for-age percentile [BMI%] ≥ 95) girls in various stages of puberty. A multivariate regression model was then constructed using free T (dependent variable), LH, insulin, pubertal group (early, mid-, or late puberty), BMI z-score, and age. Free T concentrations were highly variable among obese girls in each pubertal group. The regression model accounted for roughly half of the variability of free T in obese girls (adjusted R(2) = 0.53, P < 0.001). LH was found to have the greatest independent ability to predict free T, followed by insulin, then age and BMI z-score. Pubertal group was not an independent predictor of free T. We conclude that morning LH and fasting insulin are significant predictors of free T in obese girls, even after adjusting for potential confounders (age, pubertal group, adiposity). We suggest that abnormal LH secretion and hyperinsulinemia can promote HA in some peripubertal girls with obesity.